(untitled) - Lesikar, Raymond Vincent (New York, 2005)
Basic Business Communication by Lesikar and Flatley provides both student and instructor with all the tools needed to navigate through the complexity of the modern business communication environment.
Keywords: Commercial correspondence,English language,Business communication; Business English